Survivin inhibition with YM155 ameliorates experimental pulmonary arterial hypertension - Blanco, Isabel; Marquina, Maribel; Tura-Ceide, Olga; Ferrer, Elisabet; Ramírez, Ana M.; Lopez-Meseguer, Manuel; Callejo, Maria; Perez-Vizcaino, Francisco; Peinado, Victor Ivo; Barberà, Joan Albert (Frontiers in Pharmacology, 2023)
Background: Imbalance between cell proliferation and apoptosis underlies the development of pulmonary arterial hypertension (PAH). Current vasodilator treatment of PAH does not target the uncontrolled proliferative process in pulmonary arteries. Proteins involved in the apoptosis pathway may play a role in PAH and their inhibition might represent a potential therapeutic target. Survivin is a member of the apoptosis inhibitor protein family involved in cell proliferation. Objectives: This study aimed to explore the potential role of survivin in the pathogenesis of PAH and the effects of its inhibition. Methods: In Su5416/hypoxia-induced PAH mice we assessed the expression of survivin by immunohistochemistry, western-blot analysis, and RT-PCR; the expression of proliferation-related genes (Bcl2 and Mki67); and the effects of the survivin inhibitor YM155. In explanted lungs from patients with PAH we assessed the expression of survivin, Bcl2 and Mki67. Results: Su5416/hypoxia mice showed increased expression of survivin in pulmonary arteries and lung tissue extract, and upregulation of survivin, Bcl2 and Mki67 genes. Treatment with YM155 reduced right ventricle (RV) systolic pressure, RV thickness, pulmonary vascular remodeling, and the expression of survivin, Bcl2 and Mki67 to values similar to those in control animals. Lungs of patients with PAH also showed increased expression of survivin in pulmonary arteries and lung extract, and also that of BCL2 and MKI67 genes, compared with control lungs. Conclusions: We conclude that survivin might be involved in the pathogenesis of PAH and that its inhibition with YM155 might represent a novel therapeutic approach that warrants further evaluation.